2001
DOI: 10.1073/pnas.041610098
|View full text |Cite
|
Sign up to set email alerts
|

TRM1, a YY1-like suppressor of rbcS-m3 expression in maize mesophyll cells

Abstract: The genes rbcS and rbcL encode, respectively, the small and large subunits of the photosynthetic carbon dioxide fixation enzyme ribulose bisphosphate carboxylase͞oxygenase. There is a single rbcL gene in each chloroplast chromosome; a family of rbcS genes is located in the nuclear genome. These two genes are not ex- L eaves of C3 plants contain a single type of photosynthetic cell. Each of these cells carries on all of the reactions of oxygenic photosynthesis and contains the carbon dioxide-fixing enzyme Rubis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…Our results also are in contrast with those for ME, whose BS-specific cis-element lies within the coding region (Brown et al, 2011). Clearly, C4-specific RNA patterns arise through multiple mechanisms, as regulatory targets for transcriptional or posttranscriptional regulation have been found in the promoter region, such as the MEM1 element in the Flaveria PEPC promoter (Gowik et al, 2004), 59 UTR regions of the amaranth and Flaveria RBCS genes (Patel et al, 2004(Patel et al, , 2006, and also the coding region (ME; Brown et al, 2011) and 39 UTR (RBCS; Xu et al, 2001). …”
Section: Rbcs Expression In M Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results also are in contrast with those for ME, whose BS-specific cis-element lies within the coding region (Brown et al, 2011). Clearly, C4-specific RNA patterns arise through multiple mechanisms, as regulatory targets for transcriptional or posttranscriptional regulation have been found in the promoter region, such as the MEM1 element in the Flaveria PEPC promoter (Gowik et al, 2004), 59 UTR regions of the amaranth and Flaveria RBCS genes (Patel et al, 2004(Patel et al, , 2006, and also the coding region (ME; Brown et al, 2011) and 39 UTR (RBCS; Xu et al, 2001). …”
Section: Rbcs Expression In M Cellsmentioning
confidence: 99%
“…Early transient expression assays showed that RBCS promoter sequences alone did not confer cell type-specific expression (Bansal et al, 1992), and a 39 UTR element was subsequently found to be important for transcriptional repression in M cells (Viret et al, 1994). Repression requires sequence elements that bind the zinc finger protein TRM1 (Xu et al, 2001). Maize RBCS also appears to be regulated posttranscriptionally, and examination of RBCS cell typespecific expression in other C4 species also suggests both transcriptional and posttranscriptional mechanisms (for review, see Hibberd and Covshoff, 2010).…”
Section: Rbcs Expression In M Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Putative trans-regulators of cell-specific gene expression in maize have been identified by gel retardation assays with 59 promoter sequences of genes encoding PEPCase (Taniguchi et al, 2000), Rubisco small subunit (Xu et al, 2001), and PPdK (Matsuoka and Numazawa, 1991). However, the context in which these proteins act is not understood, and the properties of the proteins are not known.…”
Section: Cis-and Trans-regulators Of Transcriptionmentioning
confidence: 99%
“…Studies of the Ppc promoter have also revealed regulatory elements required for proper expression (Schaffner and Sheen, 1992;Kausch et al, 2001). Furthermore, nuclear-encoded transcription factors have been identified that bind specific regions of the RbcS promoter to repress M cell-specific expression (Xu et al, 2001). Transcriptional activators for Ppc also have been identified through in vitro-binding assays that may control light-and cell-specific patterns of expression (Morishima, 1998;Yanagisawa and Sheen, 1998;Yanagisawa, 2000).…”
Section: Influence Of Light Quality On Photosynthetic Differentiationmentioning
confidence: 99%